Suspected subclinical myocarditis detected by cardiac magnetic resonance imaging late post COVID-19 recovery. Issue 5 (November 2021) - Ghugre, Nilesh R.; Orbach, Ady; Biswas, Labonny; Connelly, Kim A.; Chan, Adrienne; Strauss, Bradley H.; Wright, Graham A.; Roifman, Idan
Abstract: There is growing evidence of the potential for cardiac involvement in patients who have been infected with COVID-19. In this case study, we present a patient with no history of cardiovascular disease, who was hospitalized for COVID-19 pneumonia and subsequently recovered. Despite normal serum troponin levels and left ventricular structure and function, multi-parametric cardiac magnetic resonance imaging revealed a classic myocarditis-like pattern of injury approximately 6 months after his convalescence. Physicians should be aware of the possibility of late myocardial injury/inflammation in patients with recovered COVID-19, even in the absence of elevated troponin levels and/or left ventricular dysfunction. <Learning objective: To understand the potential for COVID-19 patients to develop myocardial injury. To recognize that myocarditis can occur in patients with resolved COVID-19 infection months after resolution of the infection and in the absence of left ventricular dysfunction and troponin elevation.>